Diterpenoids from Croton crassifolius include a novel skeleton possibly generated via an intramolecular [2+2]-photocycloaddition reaction. (January 2018) - Qiu, Maosong; Jin, Jing; Zhou, Lian; Zhou, Wen; Liu, Yinxiang; Tan, Qinglong; Cao, Di; Zhao, Zhongxiang
Abstract: Five previously undescribed terpenoids (cracrosons D-H), including three clerodane diterpenoids, together with 16 known diterpenoids were isolated from Croton crassifolius (Euphorbiaceae). Cracroson D features a previously undescribed carbon skeleton with an unprecedented cyclobutane ring. Their structures, including their absolute configurations, were elucidated using spectroscopic and single-crystal X-ray diffraction analyses along with CD calculations. A plausible biogenetic pathway for cracroson D is also proposed, which was supported by the experimental results. Additionally, all of the compounds were evaluated in vitro for cytotoxicity against T24 and A549 cells using the CCK-8 method. Graphical abstract: Five previously undescribed terpenoids named cracrosons D-H, along with 16 known compounds, were isolated from the roots of Croton crassifolius . Cracroson D features a novel carbon skeleton with an unprecedented intramolecular cyclobutane ring. Image 1 Highlights: Twenty-one (five previously undescribed) terpenes were isolated from Croton crassifolius. One previously undescribed diterpenoid skeleton was isolated. The biogenetic pathway of previously undescribed carbon skeleton was proved. Several of them were cytotoxic against T24 and A549 cells.